2013
DOI: 10.1123/jsr.22.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability of Biodex System 4 Pro for Isometric Ankle-Eversion and -Inversion Measurement

Abstract: Isometric eversion and inversion testing using the Biodex 4 Pro system is a reliable method. The authors suggest that the angle of 7° of inversion is the best for isometric eversion and inversion testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The target angle was set at 15º for both eversion and inversion. Measurements were repeated 3 times, with the average difference between the self-determine and target end position calculated according to the methods of Tankevicius et al [37]. A smaller difference indicates better the joint position sense of the ankle (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target angle was set at 15º for both eversion and inversion. Measurements were repeated 3 times, with the average difference between the self-determine and target end position calculated according to the methods of Tankevicius et al [37]. A smaller difference indicates better the joint position sense of the ankle (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…A smaller difference indicates better the joint position sense of the ankle (Figure 3). Tankevicius et al [37] reported that this assessment of ankle joint position sense has high reliability, with a 95% confidence interval of intra-class correlation (ICC) scores of 0.87–0.96.…”
Section: Methodsmentioning
confidence: 99%
“…Verbal encouragement was provided. These testing procedures are similar to other studies examining isometric ankle joint torque . Maximum torque across all trials was analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were kept blindfolded throughout the examination. Tankevicius, Lankaite and Krisciunas (2013) reported the reliability scores of the Isokinetic assessment protocols, as .87-.96 ICC (intra class correlation values) with 95% confidence interval level.…”
Section: Methodsmentioning
confidence: 99%